2009
DOI: 10.1063/1.3067764
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation mechanics of copper and iron in high rate deformation tests

Abstract: Different dislocation processes are shown to be operative under high rate loading by impact-induced shock tests as compared with shockless isentropic compression experiments ͑ICEs͒. Under shock loading, the plastic deformation rate dependence of the flow stress of copper is attributed to dislocation generation at the propagating shock front, while in shockless ICEs, the rate dependence is attributed to drag-controlled mobile dislocation movement from within the originally resident dislocation density. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 21 publications
6
68
1
Order By: Relevance
“…(2.11) by 12) and to use a large enough value of the "diffusion constant" M that σ remains constant as a function of y. I have used both of these strategies for checking the accuracy of the numerical results shown in what follows. When using Eq.…”
Section: E Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…(2.11) by 12) and to use a large enough value of the "diffusion constant" M that σ remains constant as a function of y. I have used both of these strategies for checking the accuracy of the numerical results shown in what follows. When using Eq.…”
Section: E Stressmentioning
confidence: 99%
“…Thanks to the pioneering work of Kocks, Mecking, Follansbee, Meyers and others [8][9][10], we have a first-principles picture of plastic deformation in copper. (Other papers that I have found useful for understanding the present state of this field include [11][12][13].) The trouble is that copper is not observed to undergo ASB, probably because its thermal conductivity is too high.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the elastic precursor decay was attributed to the density and initial velocity of pre-existing dislocations. Armstrong et al [10] studied the dislocation relaxation mechanisms during high strain rate shock loading, concluding that dislocation generation dominates plastic relaxation under shock loading. This is because the number of pre-existing dislocations is about two to three orders of magnitude less than that generated during the shock [1,4,7].…”
mentioning
confidence: 99%
“…It has been suggested that thermo-mechanical coupling is an important ingredient in this, especially in shock waves that are strong enough to engender stresses well in excess of the elastic moduli (Wallace 1981;Kalantar et al 2005;Kadau et al 2007;Hawreliak et al 2008;Murphy et al 2010). However, it is likely that dislocation nucleation and motion is the dominant microscale phenomenon (Davison & Graham 1979;Armstrong et al 2009). Unfortunately, many different kinds of dislocation configurations are possible, such as classical slip systems involving dislocations, geometrically necessary or otherwise, partial dislocations and stacking faults, and twinned dislocations (Hirth & Lothe 1982;Armstrong et al 2009).…”
Section: Introductionmentioning
confidence: 99%